Hidrogenação eletroquímica em metais: caracterização eletroquímica e metalúrgica da formação de hidretos de Pd e Nb - Bedoch, Audrey Marie (2024)
Climate change requires a transition in the ways energy is produced and consumed. Metal hydrides (MH) can play important roles in this transition, acting as low-carbon hydrogen storage in the solid state or as energy storage in Ni-MH batteries powered by renewable sources. In this case, MHs are formed by the reaction between metal and hydrogen generated by water electrolysis in an alkaline electrolyte. The electrochemical hydrogenation of metals is a complex issue, involving phenomena described by different areas of knowledge such as electrochemistry, thermodynamics, and physical metallurgy. In this thesis, the electrochemical hydrogenation of two metals is investigated through this multidisciplinary approach. Initially, the electrochemical hydrogenation of Pd was studied, considered a model system due to its noble nature and its ability to absorb hydrogen, forming the hydride PdH0.6, which has the same crystal structure as Pd (FCC). Through the study of this model system, the concepts of reaction kinetics involved in the hydrogen evolution reaction (HER) were related to the thermodynamics and kinetics of hydrogen absorption by Pd and the formation of PdH0.6. Next, the electrochemical hydrogenation of metals was investigated in a more complex system, using the metal Nb. Nb is a body-centered cubic metal capable of absorbing hydrogen by forming two hydrides (β-NbHx orthorhombic and δ-NbH2 FCC). In addition to the formation of hydrides with different crystal structures, Nb also tends to form oxides on its surface. For Nb, the HER, thermodynamics, phase transformation mechanisms, and the impact of oxides on electrochemical hydrogenation and dehydrogenation were studied. The thickness of the Nb oxide layer increases under anodic potentials but has a limited impact on hydrogen desorption. The irreversible absorption is primarily linked to the displacive formation of the δ phase.